Significance Evaluating Coagulation-Fibrinolysis Dynamics in Chronic Thromboembolic Pulmonary Disease With Pulmonary Hypertension Caused by Heritable Thrombophilias: A Case Series - Koshi Setoyama; Takuma Ito; Rie Shirayama; Masahiro Takeo; Yutaro Naka; Hiroki Okabe; Hiroyuki Takatsu; Takumi Inami; Masaharu Kataoka (Annals of Internal Medicine: Clinical Cases)
Precisely evaluating coagulation ability is crucial for managing hypercoagulation. Antithrombin resistance is a disease in which a missense variant of the prothrombin gene, prothrombin Yukuhashi, occurs in a hypercoagulation state. We present 2 parent-child cases of antithrombin resistance-induced chronic thromboembolic pulmonary disease with pulmonary hypertension. Thromboembolic events differed between the 2 patients, suggesting differences in coagulation abilities. Rotational thromboelastometry was useful for evaluating individual coagulation–fibrinolysis dynamics. Personalized management of anticoagulation therapy based on a precise evaluation of coagulation ability is needed in hypercoagulation states.